2018
DOI: 10.1161/circresaha.117.311240
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is Required for Sortilin-Mediated Degradation of Apolipoprotein B100

Abstract: These results strongly suggest that an unconventional lysosomal targeting process dependent on autophagy degrades apoB that was diverted from the secretory pathway by sortilin and provides a mechanism contributing to the reduced LDL-C found in individuals with overexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 58 publications
(98 reference statements)
2
39
0
Order By: Relevance
“…More recently, it was shown that ATZ was delivered for lysosomal degradation after transport through the secretory pathway but was then recognized in an autophagy‐like manner, that is, one that required an ER‐phagy receptor complex . It is noteworthy that aggregated forms of ApoB, which arise when cells are treated with oxidizing agents such as polyunsaturated fatty acids, are delivered from the Golgi via autophagolysosomes for degradation in the lysosome . Similarly, degradation and refolding of the W1282X mutant appear to be modulated by small molecules that regulate the autophagy pathway as well as proteasome activity .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was shown that ATZ was delivered for lysosomal degradation after transport through the secretory pathway but was then recognized in an autophagy‐like manner, that is, one that required an ER‐phagy receptor complex . It is noteworthy that aggregated forms of ApoB, which arise when cells are treated with oxidizing agents such as polyunsaturated fatty acids, are delivered from the Golgi via autophagolysosomes for degradation in the lysosome . Similarly, degradation and refolding of the W1282X mutant appear to be modulated by small molecules that regulate the autophagy pathway as well as proteasome activity .…”
Section: Discussionmentioning
confidence: 99%
“…ApoB labeling was performed as previously described (16). Briefly, McA hepatocytes were preincubated for 2 hours in amino acid-starvation medium (DMEM without methionine/cysteine, 1% FBS, 1% Lglutamine and Penicillin/Streptomycin).…”
Section: Cell Culture Experiments -Steady-state Labeling Studies and mentioning
confidence: 99%
“…The transmembrane receptor sorting protein sortilin was also recently discovered to bind ApoB and target it for autophagic degradation, resulting in reduced LDL secretion. This may be one mechanism by which a known genetic polymorphism increasing sortilin expression substantially lowers circulating LDL levels [56]. At the receiving end, lipoproteins are endocytosed in some cell types including macrophages for subsequent lysosomal hydrolysis.…”
Section: Alternative Functions Of Autophagy Machinery In Lipid Metabomentioning
confidence: 99%